Dimensional Accuracy of Additively Manufactured Dental Models Compared with Conventional Gypsum Casts Across Different Measurement Spans: An In Vitro Study - Huamani Diaz, Leonard Walter (2026)
Accurate dental models are critical for achieving predictable outcomes in prosthodontics; however, the transition from conventional to digital workflows raises concerns regarding dimensional reliability across different clinical scenarios. This in vitro study evaluated the dimensional accuracy of conventional gypsum casts and additively manufactured dental models using standardized linear measurements derived from a metal master reference model, with particular emphasis on span-dependent behavior. Twenty definitive models were divided into 2 groups (n=10): gypsum casts obtained from addition silicone impressions and resin models fabricated through intraoral scanning followed by LCD-based 3-dimensional printing. Ten predefined linear distances were measured using a digital Vernier caliper (±0.01 mm), and deviations were calculated relative to the reference model. Statistical analysis included Shapiro–Wilk testing and independent t tests or Mann–Whitney U tests (α=.05).  Gypsum casts demonstrated significantly smaller deviations in localized measurements (0.05-0.12 mm) compared with additively manufactured models (0.22-0.44 mm) (P< .05). For inter-point distances, both workflows showed comparable performance in selected spans, whereas differences became evident in longer transverse measurements. No significant differences were observed in diagonal dimensions. Dimensional discrepancies were not uniformly distributed, indicating that measurement span influences accuracy outcomes.  Within the limitations of this study, gypsum casts remain more precise for short-span measurements, while additively manufactured models provide comparable accuracy over broader distances. Both workflows produced deviations within clinically acceptable ranges, supporting the use of additively manufactured models as a reliable alternative in digital prosthodontic workflows, particularly when full-arch spatial relationships are prioritized.